Bài giảng Kỹ thuật môi trường = Environmental engineering - Phạm Nguyệt Ánh (Trường Đại học Thuỷ Lợi, 2020)
CVEG 4098 is intended as an entry-level undergraduate course providing a scientific and engineering basis for understanding environmental issues and problems; Water and wastewater treatment, air pollution control and solid waste disposal are introduced. Upon completion, students should master the fundamental knowledge in chemical, physical and biological aspects of environmental processes, and be able to relate engineering problems to these topics.